Assessment of streamflows in the Hornád river basin and analysis of trends. Issue 1 (December 2021) - Nagy, P
Abstract: Climate change is a global phenomenon. The more frequent occurrence of dry periods, which last longer but also extreme rainfall, needs to be reduced for better water management. During the dry season, the quantity and quality of surface and groundwater decreases. Water is important for agriculture, agriculture and ecosystems. This study was focused on the occurrence of trends in daily flows in the Hornád basin at selected hydrological stations for the period 1960-2011. The Mann-Kendall trend test is used to evaluate trends in hydrometeorological time series.